Characterization of Cre Recombinase Activity for In Vivo Targeting of Adipocyte Precursor Cells - Krueger, Katherine C. (Stem Cell Reports, 2014)
The increased incidence of obesity and metabolic disease underscores the importance of elucidating the biology of adipose tissue development. The recent discovery of cell surface markers for prospective identification of adipose precursor cells (APCs) in vivo will greatly facilitate these studies, yet tools for specifically targeting these cells in vivo have not been identified. Here, we survey three transgenic mouse lines, Fabp4-Cre, PdgfRα-Cre, and Prx1-Cre, precisely assessing Cre-mediated recombination in adipose stromal populations and mature tissues. Our data provide key insights into the utility of these tools to modulate gene expression in adipose tissues. In particular, Fabp4-Cre is not effective to target APCs, nor is its activity restricted to these cells. PdgfRα-Cre directs recombination in the vast majority of APCs, but also targets other populations. In contrast, adipose expression of Prx1-Cre is chiefly limited to subcutaneous inguinal APCs, which will be valuable for dissection of APC functions among adipose depots.